Dirāsah Taḥlīlīyah Lianwā‘i “Mā” fī Matani Kitāb Ta’līm Al Muta’allim li Syaikhi Al Zarnūjī wa Ṭarīqatu Ta’līmihā - Kholifa Khusna Naim; Dewi Rusliyani (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2025)
This research aims to know the types of mā “what” in the text of the book “Ta’līm Al Muta’allim” by Sheikh Al-Zarnuji and to know the appropriate way to teach the meanings of the types of mā “what”. To achieve this, the researcher used the descriptive research method. The method of collecting data is through a desk study and documentation. The method of analysis is descriptive analysis and content analysis. After the analysis, the researcher obtained the research results as follows: The number of types of mā “what” found in the text of the book “Ta’līm Al Muta’allim” is 144 (one hundred and forty-four) forms. It has meanings: connected (91), interrogative (7), negative (15), infinitive (2), and superfluous (29). The methods of teaching grammar are often divided into two methods: the standard method and the inductive method. Each method has advantages and disadvantages, and one method cannot be preferred over the other. For students to understand the science of grammar, especially learning the rules of the types of mā “what” and their meanings easily, an appropriate method is necessary to overcome their difficulties, and this is done by not focusing on only one method, but rather combining all methods that suit the students’ needs, situations, and circumstances.